2014
DOI: 10.1111/ijpo.236
|View full text |Cite
|
Sign up to set email alerts
|

The role of exclusive breastfeeding and sugar‐sweetened beverage consumption on preschool children's weight gain

Abstract: As hypothesized, the exposure variables acted in opposite directions, but the harmful effect of SSBs intake had greater magnitude than the beneficial effect of EB on children's CWG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
12
0
4
Order By: Relevance
“…First, there may be other factors that play a more important role on development of overweight than age at complementary feeding or exclusive breastfeeding duration. One such factor might be diet quality and quantity, for which we lacked information . We found that age at complementary feeding and exclusive breastfeeding duration was weakly associated with child's BMI in groups with Turkish ethnicity, high education or maternal obesity.…”
Section: Discussionmentioning
confidence: 83%
“…First, there may be other factors that play a more important role on development of overweight than age at complementary feeding or exclusive breastfeeding duration. One such factor might be diet quality and quantity, for which we lacked information . We found that age at complementary feeding and exclusive breastfeeding duration was weakly associated with child's BMI in groups with Turkish ethnicity, high education or maternal obesity.…”
Section: Discussionmentioning
confidence: 83%
“…This formulation corrects problems such as the mean regression effect, different ages at the time of research, and collinearity of repeated measures. 5,8 Biological factors were gender, age, nutritional status and anemia; perinatal factors were birth weight, gestational age, disease at birth and reasons for hospitalization (preventable, non-preventable diseases or absence of diseases). ZBMI was used to sort nutritional status with the following cutoff points: normal weight (≤+ 1 SD), risk of overweight (>+1 SD and <+2 SD) and overweight (≥+ 2 SD).…”
Section: Methodsmentioning
confidence: 99%
“…ultraprocessed foods and sugary drinks), with subsequent total weaning of breast milk. 4,5 Such phenomena can stem from issues such as the lack of prenatal guidance or even its poor quality resulting from fragile bond between professionals and individuals. From a broader perspective, the historical role of the food industry in cultural change about infant feeding in early childhood is highlighted, through communication strategies directed at both the general population and health professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exclusive breastfeeding) and harmful (e.g. SBB consumption) risk factors for childhood obesity , randomized trials (RCTs) have offered limited evidence about the long‐term impact of reducing harmful exposures and increasing beneficial exposures either singly or in combination with each other . In addition, results from RCTs are not always generalizable to the population that would be receiving the interventions, partly because of the selective enrolment of participants into the trials .…”
Section: Introductionmentioning
confidence: 99%